Measuring service performance quality in special libraries : a case study at the Ministry of Education library - Ruzaimah binti Mohammed Zain (Kulliyyah of Information & Communication Technology, International Islamic University Malaysia, 2014)
The Educational Planning and Research Division Library (EPRD) was established as the Documentation Centre for the Malaysian Education Ministry. It was officiated by Tan Sri Dr Wan Zahid bin Mohd Noordin on 24th April 1997. Its development was initiated by the existence of the Ministry of Education (MOE) thesis database in 1995. Now, the Documentation Centre is known as the Ministry of Education Library. The main objective of the library is to establish a resource centre that holds the information resources acquired and produced by the Ministry for knowledge sharing activities. This research also measures the effectiveness of the library as a one stop reference centre by focusing on the quality of the services provided. Among the objectives of the study are 1) to assess the overall service quality of the MOE Library from the users' perspectives, 2) to assess the service quality of the MOE Library from the perspectives of different user groups and 3) to identify the problems users had encountered while getting the services at the MOE Library. In addition, in order to enhance the roles of the authorities as well as the library management towards generating knowledge and information for the Ministry of Education, this study also evaluates the management, administration and financial aspects of the library. For this research, a mixed method whereby the MOE Library is used as a case study is applied. The qualitative and quantitative data are gathered through various methods such as survey, examination of library circulation information, and many hours of personal observations. A review of the professional literature is also provided to contextualize the historical review and findings from the studies. However, the dominant form of data collection used for this research is based upon the instruments and dimensions of LibQUAL+ TM . The research samples for this study comprise of the library users which are categorized as EPRD Staff, Students and Other Library Users. This study uses the Statistical Package for the Social Sciences software in the data analysis process. Since no specific initiative has been carried out so far to measure the service quality of the Ministry of Education Library, it is vital for such a study to be conducted. It is hoped that by highlighting the underlying problems and issues, and being able to come up with constructive recommendations and solutions, immediate corrective and preventive measures could be taken by the Ministry of Education. The findings of the study hopefully will be able to provide useful information that could be used as guidelines in improving the quality of the national education standard in general and the Ministry of Education Library in particular.